Desenvolvimento de formulações para produção de grés porcelanato a partir de matérias-primas da região da bacia do Parnaíba - Luz, Jota Carlos (2008)
Brazil is a great ceramic raw materials productor because of the its big number of clay deposits, in various areas of the ceramic industry. Although, the majority of the natural reservations are unknown or not studied yet, so there is no scientific technical dates that can guide their usage and industrial application, as well as the racional and optimazed way of usage by the industrial sector. The state of Maranhão has a gigant mineral wealth as esmectite, bentonite, kaolin, clays, feldspates, marine salt, iron and others, but produce only products with small agregated value compared to the porcelanato, one of the most expensives ceramic cover tiles, the reason for that is the low water absorption (lower than 0,5%), beside present amazing tecnicals features, like mechanical resistence. The main objective of the work is to do the characterization of four clays, with the finallity of find an application by the results and develop formulations to produce porcelanato using these raw materials from Timon-MA. For this were made the raw materials characterization using X ray fluorecence; X ray diffraction; Differencial thermal analysis; Dilatometric analysis and Tecnological properties, planing three formulations that were sinterized at six different temperatures: 1150, 1170, 1190, 1210, 1230 and 1250ºC for 7 minutes. After the sinteratization, the samples were submitted to tension resistance analysis. Were attained two formulations with the requested properties to produce porcelanato